Looking for reliable answers? Westonci.ca is the ultimate Q&A platform where experts share their knowledge on various topics. Experience the convenience of getting reliable answers to your questions from a vast network of knowledgeable experts. Our platform offers a seamless experience for finding reliable answers from a network of knowledgeable professionals.
Sagot :
Sure, let's solve the equation step by step.
The equation we need to solve is:
[tex]\[ -3(x-2) + 4x = 2x - 4 \][/tex]
### Step-by-Step Solution
Step 1: Distribute
First, distribute the [tex]\(-3\)[/tex] across the terms in the parentheses on the left-hand side of the equation.
[tex]\[ -3(x - 2) + 4x = -3x + 6 + 4x = 2x - 4 \][/tex]
Step 2: Combine like terms
Next, combine like terms on the left-hand side of the equation.
[tex]\[ (-3x + 4x) + 6 = 2x - 4 \][/tex]
[tex]\[ x + 6 = 2x - 4 \][/tex]
Step 3: Isolate the variable [tex]\(x\)[/tex]
Move all [tex]\(x\)[/tex] terms to one side and constant terms to the other side. To do this, subtract [tex]\(2x\)[/tex] from both sides.
[tex]\[ x - 2x + 6 = 2x - 2x - 4 \][/tex]
[tex]\[ -x + 6 = -4 \][/tex]
Step 4: Solve for [tex]\(x\)[/tex]
Next, move the constant term from the left side to the right side of the equation by subtracting 6 from both sides.
[tex]\[ -x + 6 - 6 = -4 - 6 \][/tex]
[tex]\[ -x = -10 \][/tex]
Multiply both sides by -1 to solve for [tex]\(x\)[/tex].
[tex]\[ x = 10 \][/tex]
### Check Your Solution
To check if our solution is correct, substitute [tex]\(x = 10\)[/tex] back into the original equation and see if both sides are equal.
Original equation:
[tex]\[ -3(x-2) + 4x = 2x - 4 \][/tex]
Substitute [tex]\(x = 10\)[/tex]:
[tex]\[ -3(10-2) + 4 \cdot 10 = 2 \cdot 10 - 4 \][/tex]
[tex]\[ -3(8) + 40 = 20 - 4 \][/tex]
[tex]\[ -24 + 40 = 16 \][/tex]
[tex]\[ 16 = 16 \][/tex]
Since both sides of the equation are equal when [tex]\(x = 10\)[/tex], our solution is confirmed to be correct.
### Conclusion
\#1: We distributed the terms, combined like terms, moved all [tex]\(x\)[/tex] terms to one side and constant terms to the other, and finally solved for [tex]\(x\)[/tex].
\#2: The value of [tex]\(x\)[/tex] that makes the equation true is:
[tex]\[ x = 10 \][/tex]
\#3: Substituting [tex]\(x = 10\)[/tex] back into the original equation confirms that both sides are equal, thereby verifying our solution.
The equation we need to solve is:
[tex]\[ -3(x-2) + 4x = 2x - 4 \][/tex]
### Step-by-Step Solution
Step 1: Distribute
First, distribute the [tex]\(-3\)[/tex] across the terms in the parentheses on the left-hand side of the equation.
[tex]\[ -3(x - 2) + 4x = -3x + 6 + 4x = 2x - 4 \][/tex]
Step 2: Combine like terms
Next, combine like terms on the left-hand side of the equation.
[tex]\[ (-3x + 4x) + 6 = 2x - 4 \][/tex]
[tex]\[ x + 6 = 2x - 4 \][/tex]
Step 3: Isolate the variable [tex]\(x\)[/tex]
Move all [tex]\(x\)[/tex] terms to one side and constant terms to the other side. To do this, subtract [tex]\(2x\)[/tex] from both sides.
[tex]\[ x - 2x + 6 = 2x - 2x - 4 \][/tex]
[tex]\[ -x + 6 = -4 \][/tex]
Step 4: Solve for [tex]\(x\)[/tex]
Next, move the constant term from the left side to the right side of the equation by subtracting 6 from both sides.
[tex]\[ -x + 6 - 6 = -4 - 6 \][/tex]
[tex]\[ -x = -10 \][/tex]
Multiply both sides by -1 to solve for [tex]\(x\)[/tex].
[tex]\[ x = 10 \][/tex]
### Check Your Solution
To check if our solution is correct, substitute [tex]\(x = 10\)[/tex] back into the original equation and see if both sides are equal.
Original equation:
[tex]\[ -3(x-2) + 4x = 2x - 4 \][/tex]
Substitute [tex]\(x = 10\)[/tex]:
[tex]\[ -3(10-2) + 4 \cdot 10 = 2 \cdot 10 - 4 \][/tex]
[tex]\[ -3(8) + 40 = 20 - 4 \][/tex]
[tex]\[ -24 + 40 = 16 \][/tex]
[tex]\[ 16 = 16 \][/tex]
Since both sides of the equation are equal when [tex]\(x = 10\)[/tex], our solution is confirmed to be correct.
### Conclusion
\#1: We distributed the terms, combined like terms, moved all [tex]\(x\)[/tex] terms to one side and constant terms to the other, and finally solved for [tex]\(x\)[/tex].
\#2: The value of [tex]\(x\)[/tex] that makes the equation true is:
[tex]\[ x = 10 \][/tex]
\#3: Substituting [tex]\(x = 10\)[/tex] back into the original equation confirms that both sides are equal, thereby verifying our solution.
We hope this information was helpful. Feel free to return anytime for more answers to your questions and concerns. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for visiting Westonci.ca. Stay informed by coming back for more detailed answers.